Penerapan Ultimum Remedium terhadap Penanganan Tindak Pidana Narkoba - Wishnu Kurniawan; Tanty Susanti (Fakultas Hukum, Universitas Internasional Batam, 2016)
Law enforcement officials who have an important role to run the enforcement of criminal procedural law, one of which is the Police. Police of the Republic of Indonesia (hereinafter referred to INP) has the task, purpose, authority and responsibility which further entails also the emergence of various demands and expectations of society towards increasing INP task and oriented to the community it serves. Drug abuse among the general public is widespread especially in Batam as transit traffic of international trade.Based on this, we propose two (2) formulation of the problem addressed in this study: first, how the steps are the Indonesian National Police as investigators in tackling the problem of drug abuse and revealed in Police Barelang Batam ?, second, how the application of legal principles ultimium remedium in Law - Law Number 35 Year 2009 on Narcotics?.This study uses a conceptual foundation, juridical and theory. Juridical basis in the form of Law - Law Number 35 Year 2009 on Narcotics. Then, the theoretical basis in adoption is Theory of Law as a tool of social engineering by Roscoe Pound. This study uses normative legal research. The object of this research is in the area of Police Barelang. Therefore, methods of data analysis in this study is called qualitative descriptive.Based on this research, Steps As the Indonesian National Police and Investigators In Tackling Drug Abuse In Barelang Batam Police carried out in three parts, namely pre-emptive, preventive and repressive. The investigation process in revealing criminal cases of drug by the Drug Unit Police Barelang start of observation (review), surveillance (shadowing), undercover agents (infiltration agent), undercover buy (purchase veiled), controlled planning (submission controlled), and raid planning execution (Execution plan raids). Application of the principle of ultimum Remedium to the victims of drug abuse is not sentenced to imprisonment but rehabilitation.